If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(5a+6)=-33-7a
We simplify the equation to the form, which is simple to understand
-2(5a+6)=-33-7a
Reorder the terms in parentheses
+(-10a-12)=-33-7a
Remove unnecessary parentheses
-10a-12=-33-7a
We move all terms containing a to the left and all other terms to the right.
-10a+7a=-33+12
We simplify left and right side of the equation.
-3a=-21
We divide both sides of the equation by -3 to get a.
a=7
| -b+2=b-2(b-1) | | 3a+6b=0 | | (12x+6)(13x-1)= | | 7(x+5)-58=18 | | 2x+24=-8-4(2x-8) | | 5e=55 | | 5.9=-A-4.8 | | 2k+3-k=k+2 | | -9=1-6x+2 | | -10/2(-5)= | | 9r=-6 | | x+6=8x-15 | | 7-3x-10=-66 | | -1/6*b=3 | | 4k+3=10-3k | | -3(y+2)=-2(y+4)-y | | -3x^2=1 | | (19x+6)(20x)= | | 0=3x^2+1 | | 5m^2+13m+15=0 | | f(x)=5x^2+10x+1 | | x^3-5x^2-5x-1=0 | | 3y-9y+5w+w= | | c/4+3=8 | | 5-1k=21-3k+12 | | (51x+3)(1+52x)= | | X/8-6=8 | | 5+x/8=-3 | | (x+2x^3-3)/(x-1)=0 | | .5x+16(x+2)=48.5 | | 5x-11=10+12x | | (x+2x^3-3)/(x-1) |